(untitled) (Lex localis - Journal of Local Self-Government, 2025)
This study examines the role of Chronopolitics in development in Papua, focusing on the influence of time use on development policies and their impact on social and economic justice, as well as Papua’s position within Indonesia’s national development narrative. In this context, Chronopolitics is understood as a political instrument used to regulate the acceleration or delay of development by specific political and economic interests. Using a quantitative approach with Partial Least Squares (PLS) analysis, this study found that the use of time in Papua’s development has a significant impact on social and economic inequality in the region. The results of the analysis show that time politics in Papua has a significant contribution to inequality, where development is often slowed down, hampering economic and social progress. In addition, the issue of development in Eastern Indonesia (X2) has a greater influence on Papua’s position in the national narrative (Y), with a high R-square value (0.97), indicating that the variables analyzed can explain most of the changes in Papua’s position. This study also demonstrates that development policies that overlook local community participation exacerbate existing inequalities. Chronopolitics, through the selective use of time, influences national perceptions of Papua, which is often marginalized in national policies. These findings underscore the need for a more inclusive and socially responsible approach to achieving equitable development in Papua New Guinea.